The Process of Forming Candidate Members with Character in the Art Student Activity Unit at Universitas PGRI Sumatera Barat - Rio Yenero; Ranti Nazmi; Budi Juliardi (CV. Rayyan Dwi Bharata, 2023)
One of the organizations in West Sumatra PGRI University (UPGRISBA) is the Art Student Activity Unit (UKM). UPGRISBA Art UKM is a place where students carry out non-academic activities with the aim of self-exploration according to students' interests and talents in the arts. In carrying out activities at the UPGRISBA Art UKM, educating character in the form of discipline and responsibility is the most important element in the process of forming regeneration with character to carry out the duties and functions as a member of the UPGRISBA arts UKM. The purpose of this study is to describe the formation of the character of discipline and responsibility for prospective members of the Art Student Activity Unit at PGRI University, West Sumatra. This type of research is a qualitative descriptive research that aims to describe or describe how the process of forming prospective members with character in the Art Student Activity Unit at PGRI University, West Sumatra. The informants or resource persons in this study were active members of the PGRI University of West Sumatra Art UKM. Data collection in this study included observation, interviews with sources, and documentation. Data analysis techniques in this study started with data collection, data reduction, data presentation, and drawing conclusions. From this study it was found that the formation of the character of discipline and responsibility is very important to make a change in life. Of course, these changes require help or advice from other people, so that the first step in character building can be started by organizing. The formation of prospective members of the UPGRISBA Art UKM was not only formed in a firm way but also in a gentle way like a big brother to his younger sibling.